Evaluation of anticancer activity of Annona muricata leaf targeting FGFR3 and EGFR receptors against bladder and lung cancer - Pattilthodika Suhail, Velappan Venkatachalam Venkatachalam, Thirumalaisamy Balasubramanian, Radhakrishnan Murali, Arvind Babu Lalpet Renganathan (Journal of Applied Pharmaceutical Science, 2025)
The amplification of tyrosine kinase receptors, specifically fibroblast growth factor receptors and epidermal growth factor receptors, is primarily observed in various cancers, including bladder and lung cancer. This study aimed to identify the phytochemical components of Annona muricata leaves and evaluate their anticancer potential. The study used Q-TOF LC/MS analysis to identify phytochemical components and conducted molecular docking studies to predict the binding action of quinic acid. The largest peak was found at a retention time of 10.12 (stephabyssine), followed by 9.97 (procyanidin B2) and 11.83 (quinic acid) minutes, revealing the presence of many phytochemicals. In molecular docking studies, quinic acid was found to interact with the catalytic residues of LEU 478, ALA 557, LYS 476, and ALA 559 with hydrogen bonds, indicating hydrophobic interaction with some amino acids in the hydrophobic pockets of fibroblast-growth factor receptors 3 protein with a docking score of −9.94 Kcal/mol. It also interacts with the catalytic residues of ASP 831, THR 830, and THR 766 of the epidermal growth factor receptors proteins with a docking score of −9.103 Kcal/mol. The assessment of anticancer activity was conducted through the measurement of mitochondrial dehydrogenase activity (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay). The IC50 for MCF-7, T47D, HCT-15, and PC-3 were found to be 76.64 ± 2.56, 142.43 ± 1.86, 42.68 ± 2.89, and 152.16 ± 3.21 μg/ml, respectively. The findings were corroborated by the observed morphological alterations, including membrane blebbing, cell detachment, and rounded cell morphology in comparison to parental cells. The phytochemical analysis, including in vitro and in silico studies, identified significant constituents and key mechanisms of quinic acid as a potential anticancer agent derived from A. muricata leaves.
Keywords: Annona muricata, bladder cancer, EGFR proteins, FGFR3 proteins, lung cancer, MTT assay, molecular docking